Peran Dinas Perdagangan dan Perindustrian Provinsi Kalimantan Tengah dalam Fasilitasi Ekspor Industri Kecil dan Menengah (IKM)melalui Kegiatan Promosi Dagang pada Trade Expo Indonesia 2025 - Zahra Widya Putri; Meitiana Meitiana; Selly Aulia Margareta (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study evaluates the contribution of the Central Kalimantan Provincial Trade and Industry Office in supporting the promotion of IKM trade through the 2025 Trade Expo Indonesia (TEI). The method used is descriptive qualitative, involving interviews, observation, and document analysis. The findings indicate that Disdagperin functions as an operational organizer and technical assistant, although there are several selection stages that involve external parties. Participation in TEI 2025 has a positive impact in the form of increased product visibility, expanded global business connections, and follow-up on trade cooperation, even though the flow and process are different from previous years' TEI.